Zadovoljstvo pacientov z dostopnostjo zdravstvenih storitev v obdobju epidemije covid-19 - Plahuta, Ana (Obzornik zdravstvene nege, 2022)
Introduction: With the rapid spread of a new type of coronavirus (SARS-CoV-2) and the resulting high number of hospitalisations, public life worldwide was brought to a standstill. During the pandemic, restrictions on movement made the usual practice of visiting health facilities and receiving direct health care difficult. The aim of this study was to determine patient satisfaction with access to health services during the COVID-19 pandemic in Slovenia. Methods: A descriptive, non-experimental research method was used. The measurement instrument was an online questionnaire completed by a total of 226 respondents between December 2020 and February 2021. Data were analysed using descriptive statistics, and the non-parametric Mann-Whitney U and Kruskal Wallis test. A p-value ? 0.05 was considered significant. Results: Respondents mostly appreciated the friendly and respectful attitude of health professionals and the availability of emergency care. Inability to reach health services by telephone, waiting in waiting rooms and the short time spent in the doctor's office were negatively evaluated. The results show a slightly negative attitude towards the access to health services during the COVID-19 pandemic (Me = 86.50). The results also show a positive attitude in men regarding the access to health services (U = 1297,5, p <0.05). There were no statistically significant differences between other groups (p < 0.05). Discussion and conclusion: We found that in the time since the SARS-CoV-2 outbreak in Slovenia, trust and access to health care and health services have not changed significantly. During this time, some parts of the world have seen continued development of telemedicine, the use of which should become more prevalent in Slovenia as well. In the future, it would be useful to investigate how the pandemic has affected the psychophysical health of people in Slovenia.
Keywords: epidemija; health professionals; health system; pandemic; SARSCoV- 2; SARS-CoV-2; user satisfaction; zadovoljstvo uporabnikov; zdravstveni delavci; zdravstveni sistem